The Female Section of the Falange. Speeches and practices in Madrid - Gahete Muñoz, Soraya (Arenal. Revista de historia de las mujeres, 2015)
This paper addresses the contradictions between the speeches of Sección Femenina of Falange and their practices. It is centered on analyzing the speeches aimed at the falangist to connect to the activities carried out for they. To do this, it has been sampled of women that since 1934 to 1958, held the office of Provincial Delegates of Madrid; being the main sources used their personal files.